Patient-reported Outcomes and Quality of Life in Anemic and Symptomatic Patients With Myelofibrosis: Results From the MOMENTUM Study - Ruben A. Mesa; Claire Harrison; Jeanne M. Palmer; Vikas Gupta; Donal P. McLornan; Mary Frances McMullin; Jean-Jacques Kiladjian; Lynda Foltz; Uwe Platzbecker; Maria Laura Fox; Adam J. Mead; David M. Ross; et al. (HemaSphere, 2023)
Myelofibrosis (MF) is a chronic myeloproliferative neoplasm that typically manifests with debilitating symptoms that progressively worsen, negatively impacting patients’ quality of life. Fatigue is a multifactorial and burdensome MF-related symptom due to its severity, persistence, and prevalence, with anemia a contributing factor and major unmet need. Clinical trials of the Janus kinase (JAK)1/JAK2/activin A receptor type 1 inhibitor momelotinib have shown consistent anemia benefits, in addition to improvements in MF-related symptoms. The phase 3 MOMENTUM trial in symptomatic and anemic patients met its primary end point, with a greater proportion having a Myelofibrosis Symptom Assessment Form (MFSAF) Total Symptom Score (TSS) reduction ≥50% at week 24 with momelotinib versus danazol. To support the positive primary end point result, we conducted longitudinal, responder, and time-to-event analyses of patient-reported outcomes from MOMENTUM, as measured by the MFSAF, European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30), and Patient-Reported Outcomes Measurement Information System (PROMIS) assessments. These analyses demonstrated rapid and durable response benefits with momelotinib, with achievement of first TSS response by day 29 and continued improvement over time. Improvements favored momelotinib versus danazol for each MFSAF individual item, and greater improvements were observed for disease- and cancer-related fatigue and physical functioning at week 24, with significant results for multiple items/domains across the 3 assessments. These findings are consistent in demonstrating that momelotinib provides substantial symptom benefit.